PENGARUH PENURUNAN UNSUR MAKRO DAN PEMBERIAN ABSISIC ACID TERHADAP MULTIPLIKASI TUNAS TAPAK DARA (Vinca rosea) SECARA IN VITRO - Natalini Natalini; Kristina Kristina (Buletin Penelitian Tanaman Rempah dan Obat, 2005)
Effects of reduced–macro nutrients, and ABA to shoots multiplication of periwinkle (Vinca rosea) in vitroResearch regarding effect of reduced-macro nutrients and ABA to shoot multi-plication of periwinkle (Vinca rosea) in vitro   has been performed in the Laboratory of Germplasm and Breeding, Indonesian Spice and Medicinal Crops Research Institute, from April 2003 to March 2004. The culture media applied were  MS, ¾  and ½  MS +  (20 and 30) g/l sucrose + BA 0,1  mg/l and maintained growth inhibitor  ABA (1 and 2) mg/l. The experiment was design as a completely randomized with 10 replicated. Results showed that there was no significant different on the growth of shoots from all of MS medium until  culture 9 months with grow up to 90%. Addition ABA 1 and 2 mg/l in media,  made browning shoots until 7 months culture periods, and growing ability of 40 - 60%. Result from test of  shoots regeneration showed,  that MS + BA 0,1 mg/l + sucrose 30 g/l  (control) were the best medium for  conservation  with the highest number of shoots 8,4.